Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan terhadap Kebijakan Hutang (Studi Kasus Perusahaan Properti dan Real Estate yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) Tahun 2016 - 2020) - Martilova, Novera (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2022)
ABSTRACT This study aims to determine and analyze how much the effect of Liquidity, Profitability, and Company Size have on Debt Policy in Property and Real Estate Companies Listed on the Indonesian Sharia Stock Index (ISSI) in 2016-2020. The type of this research is quantitative approach. The data source used is secondary data obtained through the official website of the Indonesia Stock Exchange, namely IDX and IDN Financials. The population used in this study are all property and real estate companies listed on the Indonesian Sharia Stock Index (ISSI), totaling 57 companies. The sample used in this study was selected by the purposive sampling method, amounting to 11 companies. The data analysis used in this research is quantitative descriptive statistical analysis with classical assumption test, multiple linear regression analysis, coefficient of determination test and hypothesis testing. The results showed that liquidity had a significant negative effect on debt policy with a significant value of 0.000 < 0.05, profitability had a significant negative effect on debt policy with a significant value of 0.001 < 0.05, and firm size had no significant effect on debt policy with significant value of 0.396 > 0.05. Based on the results of the simultaneous test, it shows that liquidity, profitability, and firm size have a significant effect on debt policy with a significant value of 0.000 <0.05. The results of the coefficient of determination test obtained an R Square value of 0.350 or 35%.